Hemolysis and Hemoglobin Structure and Function: A Team-Based Learning Exercise for a Medical School Hematology Course - Arielle L. Langer; Eileen Scigliano (Association of American Medical Colleges, 2020)
Introduction This team-based learning (TBL) exercise focused on hemolysis and hemoglobin structure and function. The goal was to emphasize content that directly impacts clinical practice, but obliges students to understand underlying pathophysiology. The readiness assurance test (RAT) covers oxygen affinity, diagnosing hemolysis, inherited causes of hemolysis (G6PD deficiency, hereditary spherocytosis, sickle cell disease, thalassemia) and acquired causes of hemolysis (thrombotic microangiopathies, autoimmune hemolytic anemia). The application activity focused on thalassemia, sickle cell disease, and autoimmune hemolytic anemia. Methods Second-year students were divided into teams of five to six students each with one facilitator for each classroom. Students completed an individual RAT (iRAT) followed by a group RAT (gRAT). The facilitator reviewed answers of the RATs emphasizing questions where there was a lack of clarity about the correct answer. Students completed the application activity within their teams followed by a discussion guided by the facilitator. Results On average, students answered 63% of answers correctly on the iRAT. The average team score on the gRAT was 26.7 out of 30 points. The session was well reviewed by both students and facilitators. Students ranked the quality of all facilitators as excellent with an average rating of 4.4 of 5. Exam scores improved compared to prior to the introduction of TBL, but this was also found for material not covered. Discussion The use of TBL to emphasize the relationship between pathophysiology and the diagnosis and management of patients was both an effective teaching method and a successful way to engage medical students.